ANALYSIS THE FACTORS INFLUENCE CONSUMER BUYING DECISION ON ONLINE SHOPPING CLOTHING FOR CONSUMER IN MANADO - Indriani, Ida Ayu Debora (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Marketing is an important thing for marketer in order to achieve the organizational goals. Marketing is the process of creating, communicating, and delivering products or services that have value for customers. Marketing nowadays has entered modern phase, consumer can buy products from virtual store as one of shopping channels. With a good implementation of marketing strategies can affect a good communication between organization and target markets. This research is designed to analyze the factors influence the buying decision on online shopping clothing for consumer in Manado using Factor Analysis for data reduction that summarizes the observed factors. The finding resulted all factors are qualified, and the three most dominant factors based on communality test are Available Products (0.836), followed by Refund (0.812) and Perceived Ease of Use (0.810). Available products as the most dominant factor, there are varieties of products only offered online and unlimited stocks of each product. Refund as the second most dominant factor which enable the consumer to replace the product that didn’t meet their requirements. Perceived Ease of use as the third most dominant factor means that consumer choose to shop online because it is free of effort. Online shop should provide pre-order service with quick production period to fulfill consumer needs when the product is out of stock. Keywords: consumer buying decision, online shopping